Planning for quality and sustainable sanitation infrastructure post-apartheid South Africa: insights from Cosmo City - Mathonsi, Mthabisi V.; Mphambukeli, Thulisile N.; Mufungizi, Andisa A. (Frontiers in Sustainable Resource Management, 2025)
The extent to which apartheid policies deliberately affected and disadvantaged the non-white race through racial planning enabled this paper to explore the strategies employed in the development of sanitation infrastructure in post-apartheid South Africa. Racial spatial planning and infrastructure neglect in disadvantaged settlements created deep-rooted historical injustices that are still entrenched in the post-apartheid era. The post-apartheid government has implemented various measures and strategies intended to address these historical imbalances. However, the gaps and challenges that the disadvantaged communities experienced in the pre-apartheid regime are being perpetuated by the post-apartheid government. It is clear that the pre-apartheid regime set the stage, and the post-apartheid government did less to break or redress systemic failure. The provisions of inclusive, reliable, and sustainable sanitation infrastructure remain a critical concern today. Systemic gaps and spatial injustices are evident within communities. Cosmo City in Johannesburg is experiencing these systemic challenges in the form of deteriorating infrastructure, legacies of infrastructural neglect, and incapacitated institutions meant to address the needs of the communities. The study employed a qualitative method where qualitative interviews, observations, policy and planning analysis, and a literature review were conducted. The study findings showed the complexity and interrelated issues of planning for quality and sustainable sanitation infrastructure, which expose limited financing, inadequate institutional capacity, and political will. These issues have highlighted a lasting impact on social wellbeing, the environment, health, and implementation. The study contributed to various lessons, such as the impact of community engagement and participation in decision-making processes in fostering project ownership, acceptance, and sustainable objectives and success.